The ’Bumiputera Policy’: Dynamics and Dilemmas - Richard Mason; Ariffin Omar (Kajian Malaysia, 2003)
The papers in this volume were presented at a three-days seminar on "The 'Bumiputera Policy' : Dynamics and Dilemmas" in Penang, 23-25, September 2003. The seminar was hosted by the School of Humanities, under the auspices of the office of the Vice-Chancellor, Universiti Sains Malaysia (USM). The idea of putting together such a seminar occrred to us soon after the United Malays National Organisation (UMNO) Triennial General Meeting in 1999, in which Dato'Seri Dr. Mahathir Mohamad, then President of UMNO, and Prime Minister of Malaysia, issued "a wakee-up call" to the Malays, reminding them that comes the year 2000, the National Development Policy (NDP) (1991-2000) would expire and aspects of the policy pertaining to the special position of the Malays would be reviewed. The NDP was a continuation of the New Economic Policy (NEP) after the latter policy lapsed in 1991. We thought it might be useful to organize a seminar to reflect upon avhievements, effectiveness, shortcomings and ramifications of what we called the " Bumiputera Policy". The importance of the seminar is underscored by the fact that an intergrade seminar on this important contemporary topic has not be done before. All our colleagues whom we approached regarding the seminar agreed that such a seminar would be important and timely.